2017
DOI: 10.3390/ma10091093
|View full text |Cite
|
Sign up to set email alerts
|

Large Electrocaloric Effect in Lead-Free (Ba0.85Ca0.15)(Zr0.1Ti0.9)O3 Ceramics Prepared via Citrate Route

Abstract: Abstract:The 1 wt % Li-doped (Ba 0.85 Ca 0.15 )(Zr 0.1 Ti 0.9 )O 3 (BCZT-Li) ceramics prepared by the citrate method exhibit improved phase purity, densification and electrical properties, which provide prospective possibility to develop high-performance electrocaloric materials. The electrocaloric effect was evaluated by phenomenological method, and the BCZT-Li ceramics present large electrocaloric temperature change ∆T, especially large electrocaloric responsibility ξ = ∆T max /∆E max , which can be comparab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 36 publications
(81 reference statements)
1
11
0
Order By: Relevance
“…Here ρ is the density of the ceramics is noted 5.9 g cm −3 for NBNT‐Nb‐0 and 5.82 g cm −3 for NBNT‐Nb‐1with the help of Archimedes method, respectively. The observed values are found to be very close to the pure NBT based ceramics . The electrocaloric temperature variation (Δ T ) as a function of temperature for both ceramics, obtained with varies in electric fields as shown in Figure a,b.…”
Section: Resultssupporting
confidence: 59%
“…Here ρ is the density of the ceramics is noted 5.9 g cm −3 for NBNT‐Nb‐0 and 5.82 g cm −3 for NBNT‐Nb‐1with the help of Archimedes method, respectively. The observed values are found to be very close to the pure NBT based ceramics . The electrocaloric temperature variation (Δ T ) as a function of temperature for both ceramics, obtained with varies in electric fields as shown in Figure a,b.…”
Section: Resultssupporting
confidence: 59%
“…In contrast, very slim loops appeared, corresponding to the existence of ferroelectric clusters or residual polar nanoregions (PNR), [58][59][60] oen attributed to the relaxor behavior. 29 The temperaturedependence of the energy storage performances of the BCZT ceramic at 60 kV cm À1 is presented in Fig. 6b.…”
Section: 32mentioning
confidence: 99%
“…26 The electrocaloric effect (ECE) in BCZT relaxor ferroelectric ceramics has been widely investigated. 15,[27][28][29][30][31] Kaddoussi et al 12 studied the ECE in Ba 0.85 Ca 0.15 Zr 0.10 Ti 0.90 O 3 indirectly using the Maxwell relation at 8 kV cm À1 , and found a low electrocaloric temperature change (DT) of 0.152 K. Using the same approach, Ben Abdessalem et al 28 obtained DT ¼ 0.565 K at 30 kV cm À1 . Zhou et al 32 studied the compositional dependence of the electrocaloric effect in lead-free (1 À x)Ba(Zr 0.20 Ti 0.80 )O 3x(Ba 0.70 Ca 0.30 )TiO 3 ceramics under a moderate electric eld of 28 kV cm À1 , and reported a high ECE response of 0.56 K at x ¼ 0.6.…”
Section: Introductionmentioning
confidence: 99%
“…For eco-friendly solid-state refrigeration, BCZT ceramic demonstrated enhanced electrocaloric properties. 13,[16][17][18][19][20][21] Zhou et al 18 investigated the electrocaloric effect (ECE) in lead-free (1 À x)BZT-xBCT system under a moderate electric eld of 28 kV cm À1 and reported high ECE response of 0.56 K at x ¼ 0.6. In addition, Ben Abdessalem et al 22 studied the electrocaloric effect (ECE) in BCZT indirectly using Maxwell relation under 30 kV cm À1 and obtained DT ¼ 0.565 K around T C ¼ 119 C. Besides, Hanani et al 11 reported a signicant electrocaloric temperature change (DT) of 1.479 K with remarkable refrigerant capacity (RC) of 140.33 J kg À1 , and a high coefficient of performance (COP ¼ input power/output cooling power) 23 of 6.29 under 55 kV cm À1 .…”
Section: Introductionmentioning
confidence: 99%